AN UNDERSTANDING OF FGM (FEMALE GENITAL MUTILATION): WOMEN OF THE ‘BOHRA COMMUNITY’ WHO ARE CIRCUMCISED AND IT’S SOCIO-SEXUAL EFFECTS - Syyed, Huda (PEOPLE: International Journal of Social Sciences, 2019)
The strive for women’s emancipation and equal rights recently emerged as a topic of major concern within the socio-cultural arena of developing countries, such as Pakistan. Lack of awareness and cultural conditioning fosters an unsafe environment towards young girls and women. They are marginalized to challenges of honour killing, forced marriages and ‘Female Genital Mutilation (FGM)’. The latter, remains a widely unknown and overlooked issue within Pakistani society. This paper critically analyzes FGM/C as a physically invasive procedure practiced amongst women, that belong to a tight-knit community of “Dawoodi Bohra Muslims”, in Pakistan. They are considered a sub-sect of Shi’ite Muslims whose roots are thought to be tracked back to regions of Yemen or Egypt, it is also suggested that some of their ancestors might have belonged to African origins. An insider versus outsider approach will explore how FGM/C is not a normalized practice in outsider communities and is seen as a clear violation of human rights by the United Nations. Comparative investigation includes surface revision of quantitative and qualitative data to understand social, psychological and sexual after-effects. Furthermore, collection of primary source surveys and semi-structured interviews enunciate reasons as to why the community practices this ritual. To better tackle themes of gender discrimination, it is imperative to pursue in-depth studies of the religious removal or alteration of clitoris and/or labia from the female anatomy and how it curbs sexual pleasure of women. This topic scrutinizes that a mixed methodology approach allows tolerant comprehension of female circumcision, yet does not nullify acknowledgment of its patriarchal roots and violent nature. Lastly, it will emphasize that cultural male domination can control and morph a woman’s sexual identity. This research topic could contribute towards humanitarian information and approaches which could improve the situation of women that undergo FGM/C.